If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x)(x) + x + 4 = 60 Multiply x * x x2 + x + 4 = 60 Reorder the terms: 4 + x + x2 = 60 Solving 4 + x + x2 = 60 Solving for variable 'x'. Reorder the terms: 4 + -60 + x + x2 = 60 + -60 Combine like terms: 4 + -60 = -56 -56 + x + x2 = 60 + -60 Combine like terms: 60 + -60 = 0 -56 + x + x2 = 0 Factor a trinomial. (-8 + -1x)(7 + -1x) = 0Subproblem 1
Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8Subproblem 2
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Solution
x = {-8, 7}
| 5x-2.1=62.5 | | (2y+2y)+(4x+4x)=30 | | 2(4y-3)=3(y+5) | | 2x+57=33findx | | u+3.14=70 | | 2x+57=33 | | (x+2i)(x-2i)(x+4)=0 | | 6=J-5 | | 3y+7=2x-5 | | N/10-20=20 | | 100x-40y=320 | | 6x7/8= | | 3z+5z=0.6 | | (n)(n)+72=-17n | | 3x-5=6+x | | 6x+7=3(2x+4) | | (k)(k)-11k+30=0 | | (12y)(12y)+40y=7 | | 3x^2-8+5x=0 | | 3x+6=507 | | 10/3x1/2 | | 6d+4=-32 | | 5/6z=5/7 | | 18/sin40 | | a=bd | | p^2-14p=51 | | (d)(d)=5d | | 10c/2-32/4=56/8 | | (w)(w)=12 | | 3/7x1/7 | | 6-9(1-7n)=-21 | | -4x-16y=-12 |